2018
DOI: 10.18320/jimd/201704.0376
|View full text |Cite
|
Sign up to set email alerts
|

2. A study about knowledge and awareness regarding post-extraction complications among dental interns of the College of Dentistry

Abstract: Abstract:Background: The most common dental procedure done in the dental clinics is the extraction of teeth. Each dental practitioner should know the various complications that can happen during these procedures. Having the basic knowledge and awareness of these post-extraction complications can prevent the future untoward effects on the patients. Increased awareness and knowledge can decrease the incidence of post-extraction complications. The aims of the study was to find out the knowledge and awareness of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…to evaluate the knowledge of dental students regarding post extraction complications found 78.3% agreed for the usefulness of thorough medical history for treating complications [12]. In our study, various post extraction complications observed were pain (25.4%), prolonged bleeding (19.3%), swelling (8.6%), dry socket (6.7%).…”
Section: Low the Total Number Of Responses Is Shown In The Fig Belowmentioning
confidence: 51%
“…to evaluate the knowledge of dental students regarding post extraction complications found 78.3% agreed for the usefulness of thorough medical history for treating complications [12]. In our study, various post extraction complications observed were pain (25.4%), prolonged bleeding (19.3%), swelling (8.6%), dry socket (6.7%).…”
Section: Low the Total Number Of Responses Is Shown In The Fig Belowmentioning
confidence: 51%
“…Other researchers reported level of PEPK were higher among female patients as compared to male patients [13,14]. It was also observed women were significantly more anxious than men [15,16].…”
Section: Discussionmentioning
confidence: 84%
“…Some researchers reported females were more conscious about their oral health and they used to listen very carefully and practiced it [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of our interns and senior students is fair for the most common postextraction complications, but it is less than the study conducted by Derrbishi et al ., 2017. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…Extraction is a very common procedure in dental clinics worldwide. [ 3 4 ] Extraction can be of two types, simple and transalveolar extractions. Teeth are extracted for a variety of reasons such as caries, pulpal necrosis, periodontal disease, orthodontic reasons, malposed teeth, cracked teeth, impacted teeth, supernumerary teeth, teeth associated with pathologic lesions, radiation therapy, teeth involved in jaw fractures, and financial issues.…”
Section: Introductionmentioning
confidence: 99%